Elementary Geometry for College Students (6th Edition)

Published by Brooks Cole
ISBN 10:
ISBN 13:

Chapter - Section 11.4 - Applications with Acute Triangles - Exercises - Page 521: 38

Answer

$c^{2}= a^{2} +b^{2}- 2\times a \times b \times 0= c^{2}= a^{2} +b^{2}$

Work Step by Step

If $\gamma = 90^{\circ}$, then $\cos \gamma =0$ Therefore, if we replace $\cos \gamma$ by 0 in the equation, we get $c^{2}= a^{2} +b^{2}- 2\times a \times b \times 0$ $ c^{2}= a^{2} +b^{2}$ And that is the Pythagorean Theorem
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.